If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2g + 8 = g Reorder the terms: 8 + 2g = g Solving 8 + 2g = g Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-1g' to each side of the equation. 8 + 2g + -1g = g + -1g Combine like terms: 2g + -1g = 1g 8 + 1g = g + -1g Combine like terms: g + -1g = 0 8 + 1g = 0 Add '-8' to each side of the equation. 8 + -8 + 1g = 0 + -8 Combine like terms: 8 + -8 = 0 0 + 1g = 0 + -8 1g = 0 + -8 Combine like terms: 0 + -8 = -8 1g = -8 Divide each side by '1'. g = -8 Simplifying g = -8
| -6z=-5z-6 | | 5y+1.8=4y-3,2 | | -2y=6-3y | | 9x+100=8x+211111 | | 2(x+5)-(2x+10)=0 | | z^3-3z^2+z-3i=0 | | .5x+7=23 | | 4k=-6+3k | | .66x+2=5 | | 5(x+2)=(5x+10) | | 9x+100=8x+21 | | 386*0.5t-16t^2=0 | | 5b-5-8b-6= | | -10u+7= | | 5x+3=7-x | | 12-9x=199+2x | | 7x-4-7x-8=5x-5x-15 | | 61+53= | | 9b-6=5b+18 | | (x^3+3x^2-x+5)(-x^2+5)= | | -0.20(40)+0.70x=0.30(40+x) | | 3x^2-6x-6=0 | | 2y^2-16y=-32 | | 7+5s=6s | | 4x^2+324=0 | | 4x-186=129+x | | .25x-.25=-4 | | 8-3*x=-1 | | N(9)=60p-p^2 | | 9b-6=5b+1b | | 4(2z-2)=7(z-3) | | 2x-4+10=5x |